Comparison of different optimization and process control procedures - Marko Reibenschuh; Franc Cus; Uros Zuperl (Journal of Industrial Engineering and Management (JIEM), 2010)
This paper includes a comparison of different optimization methods, used for optimizing the cutting conditions during milling. It includes also a part of using soft computer techniques in process control procedures. Milling is a cutting procedure dependent of a number of variables. These variables are dependent from each other in consequence, if we change one variable, the others change too. PSO and GA algorithm are applied to the CNC milling program to improve cutting conditions, improve end finishing, reduce tool wear and reduce the stress on the tool, the machine and the machined part. At the end a summary will be given of pasted and future researches.
Keywords: 650; optimization; milling; cutting parameters; LENS